Clinicopathological and prognostic significance of mTOR and phosphorylated mTOR expression in patients with esophageal squamous cell carcinoma: a systematic review and meta-analysis. Issue 1 (December 2016) - Li, Shuangjiang; Wang, Zhiqiang; Huang, Jian; Cheng, Shan; Du, Heng; Che, Guowei; Peng, Yong
Abstract Background Mammalian target of rapamycin (mTOR) is a serine/threonine protein kinase responsible for regulating ribosomal biogenesis and protein synthesis. Dysregulation of mTOR contributes to tumorigenesis, angiogenesis, cellular growth and metastasis but its roles in esophageal squamous cell carcinoma (ESCC) are controversial. Therefore, the objective of this study is to evaluate the prognostic and clinicopathological significance of mTOR/p-mTOR expression in ESCC. Methods Literature retrieval was conducted by searching PubMed, EMBASE and the Web of Science for full-text papers that met our eligibility criteria. Odds ratio (OR) and hazard ratio (HR) with 95 % confidence interval (CI) served as the appropriate summarized statistics for assessments of clinicopathological and prognostic significance, respectively. Cochrane Q-test and I2 -statistic were adopted to estimate the heterogeneity level between studies. Potential publication bias was detected by Begg's test and Egger's test. Results A total of 915 ESCC patients from nine original articles were included into this meta-analysis. The pooled analyses suggested that mTOR/p-mTOR expression was significantly correlated with the unfavorable outcomes of differentiation degree (OR: 2.63; 95 % CI: 1.71–4.05;P  = 0.001), tumor invasion (OR: 1.48; 95 % CI: 1.02–2.13;P  = 0.037), TNM stage (OR: 2.25; 95 % CI: 1.05–4.82;P  = 0.037) and lymph node metastasis (OR: 1.82; 95 % CI: 1.06–3.11;P  = 0.029), but had no significant relationship to the genders (OR: 0.81; 95 % CI: 0.50–1.32;P  = 0.396). Moreover, mTOR/p-mTOR expression could independently predict the worse overall survival (HR: 2.04; 95 % CI: 1.58–2.62;P  < 0.001), disease-free survival (HR: 2.39; 95 % CI: 1.64–3.49;P  < 0.001) and cancer-specific survival (HR: 1.62; 95 % CI: 1.18–2.23;P  = 0.003) of patients with ESCC. Such prognostic value of mTOR was not substantially altered by further subgroup analyses. Conclusions Positive expression of mTOR and p-mTOR was significantly associated with the unfavorable conditions on the depth of tumor invasion, TNM stage, differentiation degree and lymph node metastasis. mTOR and p-mTOR could serve as a valuable predictor for the poor prognosis of ESCC. More high-quality worldwide studies performing a multivariate analysis based on larger sample size are urgently required for further verifying and modifying our findings in the future.